If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -5) = -6 Reorder the terms: 6(-5 + y) = -6 (-5 * 6 + y * 6) = -6 (-30 + 6y) = -6 Solving -30 + 6y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 6y = -6 + 30 Combine like terms: -30 + 30 = 0 0 + 6y = -6 + 30 6y = -6 + 30 Combine like terms: -6 + 30 = 24 6y = 24 Divide each side by '6'. y = 4 Simplifying y = 4
| 5(y+3)=55 | | b^2-4*b+4=0 | | 8x-32=18+6x | | 2x+8-4x-15=16+8x-2-3 | | (3x+6)= | | y=(3x/12)+105 | | 2(x-6)+3x=8 | | 3x+30=90 | | (x^2+2x+1)(x^2+5x+4)=0 | | y=3x/12+105 | | 18-2x=2x+2 | | (y+5)(y^2-5y+25)= | | 1+6x-3x=19 | | 3x+35=13x-56 | | 4*1/2-1/3 | | 6x+17=65+3x | | (3x+30)= | | (x+-7)(x+-7)=14x | | 2(a-2)=-(a-1)/(a-4) | | X^2(5x+3)=26x | | 4x-4=2x+14 | | 1/3+2x=5/12 | | 8X-5Y-3=0 | | 50=9x+5 | | 3(2x-1)=2(4x-7) | | 0.3x+33.6=51 | | 7x-10=x+2 | | 7.3x-5.8+2.5x= | | F(x)=2x^2+5x+9 | | 56=24(1/6z+5/6) | | 8x=27-x | | H=-16t^2+72t+3 |